The Relationship Of Nurses' Knowledge With The Implementation Of Sop For Providing Entral Nutrition Therapy In The ICU Room, Dr. Hospital. Zainoel Abidin Government Of Aceh 2023 - Nasution, Nurromsyah; Satria, Orita; Rosita, Erlia (Institute Of Computer Science (IOCS), 2024)
Nutrition is one of the most important aspects of medical care for critically ill patients, especially in the ICU. Enteral nutrition is the method used for delivery that supplies all the nutrients. This study aims to determine the relationship between nurses' knowledge and the implementation of SOPs for providing enteral nutrition therapy in the ICU. Correlative Descriptive research type with a Cross Sectional approach. The research sample was 34 respondents using total sampling technique. Data analysis used the chi square test with a significance level of ?= 0.05 (95%). The results of the research obtained nurses' knowledge of implementing SOP for enteral administration (p = 0.000 < ? 0.05). The results of this study indicate that nurses' knowledge can influence the application of SOPs in providing enteral nutrition to patients treated in the ICU